2020
DOI: 10.1002/cche.10276
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gluten on rheological properties of dough and qualities of noodles with potato–wheat flour blends

Abstract: Background and objectives:The effects of gluten on rheological properties of dough and qualities of noodles with potato-wheat formulated flour blends were investigated with the objective of developing and optimizing formulation. Findings: Using a formulated flour with potato mass ratio of 30% as the base flour and varying gluten addition, it was shown that addition of wheat gluten at levels of 7.0%-9.0% not only improved rheological properties of the formulated flour, but also improved the textural properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Addition of gluten proteins to whole‐wheat flour produces malleable whole‐wheat bread. The use of gluten proteins improves the rheological properties of potato‐wheat blends and also improves the structural properties of noodles (Zhao et al ., 2020). The addition of 2%–4% gluten proteins to buckwheat flour reduced the rate of cooking loss in noodles (Thanushree et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Addition of gluten proteins to whole‐wheat flour produces malleable whole‐wheat bread. The use of gluten proteins improves the rheological properties of potato‐wheat blends and also improves the structural properties of noodles (Zhao et al ., 2020). The addition of 2%–4% gluten proteins to buckwheat flour reduced the rate of cooking loss in noodles (Thanushree et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Javaid et al (2018) reported that adding 0.6% xanthan gum increased the cohesiveness of nonfried instant potato noodles, but the cooking loss increased at the same time. Addition of 7.0–9.0% gluten improved the rheological properties of dough and the eating qualities of noodles added with 30% potato flour, but the overall quality is still not good enough (Zhao et al, 2020). Therefore, the innovation of technology to improve the processing and eating qualities of potato noodles is still a challenging issue.…”
Section: Introductionmentioning
confidence: 99%